Pengembangan Media Blooket Web Game untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris Kelas I Sekolah Dasar - Hanan Salsabila Maulana; Novanita Whindi Arini (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The aim of this study is to find out how much improvement there has been in students has been in students mastery of English vocabulary. Research that focuses on mastering English vocabulary in elementary schools using the Blooket Web Game. The 4-D model is the approach used, namely define, design, developm, and disseminate. The research sample consisted of 52 people divided into three trials, namely 32 people for the pretest and posttest assessment, then 5 people for the small test assessment, 15 people for the large test assessment. Based on the analysis results obtained, it seen from the analysis of students need, then a student respon questionnaire and validator questionnaire are filled in. So, it can be accumulated that the development of the Blooket Web Game obtained the “Very Eligible” category with a score of 87.20% from the small group, and a score of 94.6% from the large group, while from the questionnaire the student respon reached 93.20%. Therefore, it can be concluded that the Blooket Web Game is in the “Very Appropriate” category and can be used a as media tool during learning activities.